Pengembangan Sistem Informasi Kesbangpol Kota Palembang Untuk Pengelolaan Organisasi Kemasyarakatan - Muhammad Saripudin; Kurniawan Kurniawan (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
The National Unity and Politics Agency (Kesbangpol) is a government agency mandated to provide guidance, supervision, and data management for mass organizations. The results of the information collection revealed several fundamental problems, including inefficient administrative processes where the registration and verification of mass organizations require the collection and validation of large amounts of documents. If done manually, this stage is very time-consuming and labor-intensive, both for Kesbangpol officers and mass organization administrators. The purpose of this study is to build a centralized database that stores all mass organization information in a structured, integrated manner, and to develop an information system capable of transforming mass organization management at Kesbangpol. The system development method used is the SDLC method including analysis, design, coding and testing, and implementation. The results of this study provide a single source of accurate and real-time data, facilitate access for authorized parties and minimize data errors, strengthen Kesbangpol's supervisory function and encourage mass organizations to be more transparent and responsible in carrying out their activities, making it easier to verify the status of mass organizations, access activity reports, and monitor their compliance with applicable regulations.